1998
DOI: 10.1111/j.1651-2227.1998.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult height comparison between boys and girls with precocious puberty after long‐term gonadotrophin‐releasing hormone analogue therapy

Abstract: Adult height comparison between boys and girls with precocious puberty after long-term gonadotrophin-releasing hormone analogue therapy. Acta Paediatr 1998; 87: 521-7. Stockholm. ISSN 0803-5253 We examined 22 girls and 11 boys with idiopathic precocious puberty (IPP) treated with a GnRH analogue for a period of about 4 y. The purpose of our study was to evaluate possible differences between the two sexes in bone growth and skeletal maturation during treatment and in the achievement of final height, and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…In Europe, the 11 boys reported by Galluzzi et al [24], all with idiopathic CPP and treated with triptorelin depot, showed a final height exceeding the initial prediction by 6.7 cm and were close to target height (Table 4). In subsequent studies from Europe, Israel, and India, all using triptorelin depot, the adult height was greater than the target height [23,[44][45][46].…”
Section: End Results In Boys With Central Precocious Puberty Treated mentioning
confidence: 76%
See 2 more Smart Citations
“…In Europe, the 11 boys reported by Galluzzi et al [24], all with idiopathic CPP and treated with triptorelin depot, showed a final height exceeding the initial prediction by 6.7 cm and were close to target height (Table 4). In subsequent studies from Europe, Israel, and India, all using triptorelin depot, the adult height was greater than the target height [23,[44][45][46].…”
Section: End Results In Boys With Central Precocious Puberty Treated mentioning
confidence: 76%
“…In Europe, triptorelin depot is widely used at 28 day intervals [15,[22][23][24][25], even though some authors have reported shorter frequency intervals of administration (21-26 days) [26][27][28]. It is usually administered at a dose of 3.75 mg (approximately 60-75 μg/kg) for children weighting more than 20 kg [22][23][24][25]; a half dose has been employed in patients weighting less than 20 kg [23]. Some authors have used higher doses (90-100 μg/kg) [28,29].…”
Section: Authormentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been suggested that treatment with GnRHa improves final adult height, the evidence points more to the age at the onset of treatment as the crucial factor [113][114][115], with a more clearcut effect in younger children. Data on final height suggest that treatment with GnRHa analogs and cyproterone acetate cannot recover lost height potential, and children cannot attain their target mid-parental height [116,117].…”
Section: Gonadotropin-dependent Precocious Pubertymentioning
confidence: 99%
“…However, withdrawal of sex steroids due to GnRHa results in a reduction in bone mineral density [122,123], although there are no long-term data on how this translates into long-term bone health [115]. Sex steroid withdrawal in children can result in "menopausal" symptoms, such as hot flushes and mood swings, occasionally necessitating low-dose estrogen therapy.…”
Section: Gonadotropin-dependent Precocious Pubertymentioning
confidence: 99%